LSM12 and ME31B/DDX6 Define Distinct Modes of Posttranscriptional Regulation by ATAXIN-2 Protein Complex in Drosophila Circadian Pacemaker Neurons. - Lee, J.; Yoo, E.; Lee, H.; Park, K.; Hur, J.H.; Lim, C. (Molecular Cell, 2017)
ATAXIN-2 (ATX2) has been implicated in human neurodegenerative diseases, yet it remains elusive how ATX2 assembles specific protein complexes to execute its physiological roles. Here we employ the posttranscriptional co-activator function of Drosophila ATX2 to demonstrate that LSM12 and ME31B/DDX6 are two ATX2-associating factors crucial for sustaining circadian rhythms. LSM12 acts as a molecular adaptor for the recruitment of TWENTY-FOUR (TYF) to ATX2. The ATX2-LSM12-TYF complex thereby stimulates TYF-dependent translation of the rate-limiting clock gene period (per) to maintain 24 hr periodicity in circadian behaviors. In contrast, ATX2 contributes to NOT1-mediated gene silencing and associates with NOT1 in a ME31B/DDX6-dependent manner. The ME31B/DDX6-NOT1 complex does not affect PER translation but supports high-amplitude behavioral rhythms along with ATX2, indicating a PER-independent clock function of ATX2. Taken together, these data suggest that the ATX2 complex may switch distinct modes of posttranscriptional regulation through its associating factors to control circadian clocks and ATX2-related physiology.